Depolymerization of bagasse by Ruminococcus albus in the production of eco-friendly fuel - Mutalik, Sampana; C.S, Vinod Kumar; Swamy, Subramanya; S, Manjappa (Research in Biotechnology, 2011)
Ethanol production by fermentation of lignocellulosic biomass-derived sugars involves a fairly ancient art and an ever-evolving science. Production of ethanol from lignocellulosic biomass is not avant-garde, and wood ethanol plants have been in existence since at least 1915. Most current ethanol production relies on starch- and sugarbased crops as the substrate; however, limitations of these materials and competing value for human and animal feeds is renewing interest in lignocelluloseÃ‚Â conversion. Lignocellulosic biomass contains carbohydrate fractions that can be converted into ethanol. In order to convert these fractions, the cellulose and hemicelluloses must ultimately be converted or hydrolysed into monosaccharides; it is the hydrolysis that has historically proven to be problematic. Biologically mediated processes are promising for energy conversion, in particular for the conversion of lignocellulosic biomass intoÃ‚Â fuels. The objective of the present study is to optimise cellulosic ethanol production from bagasse by using Ruminococcus albus isolated from rumen of herbivores animals. The processing and utilization of theÃ‚Â lignocellulosic substrate is complex, differing in many aspects from crop-based ethanol production. Since the scientific dogma states that the breakdown or depolymerisation of lignocellulose can be achieved only by chemical or by enzymatic approach; in the present study we isolated Ruminococcus albus from rumen animals which was depolymerise cellulose and hemicellulose as well as to tolerate stress conditions. Optimum temperature, pH and substrate concentration for depolymerization were 390C, 8.8 and 3.5% respectively for Ruminococcus albus. For the feedÃ‚Â stock of concentration 3.5%, ethanol yield of 19.8g/l was obtained.